1999
DOI: 10.1038/43830
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase I transduces Wnt signals

Abstract: The Wnt signalling cascade is essential for the development of both invertebrates and vertebrates, and is altered during tumorigenesis. Although a general framework for Wnt signalling has been elucidated, not all of the components have been identified. Here we describe a serine kinase, casein kinase I (CKI), which was isolated by expression cloning in Xenopus embryos. CKI reproduces several properties of Wnt signals, including generation of complete dorsal axes, stabilization of beta-catenin and induction of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
408
4
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(428 citation statements)
references
References 48 publications
13
408
4
1
Order By: Relevance
“…However, evidence exists that the DEP domain influences b-catenin signaling (Wong et al 2000;Simons et al 2009;Tauriello et al 2012). DVL associates with kinases such as CK11 and CK2, and becomes hyperphosphorylated upon Wnt signaling (Willert et al 1997;Peters et al 1999;Kishida et al 2001;Cong et al 2004a;Klein et al 2006). These kinases, in particular CK11, have been documented to have activating roles in Wnt/b-catenin signaling, but the role of DVL phosphorylation remains unclear.…”
Section: The Wnt -Fzd -Lrp5/6 Complexmentioning
confidence: 99%
“…However, evidence exists that the DEP domain influences b-catenin signaling (Wong et al 2000;Simons et al 2009;Tauriello et al 2012). DVL associates with kinases such as CK11 and CK2, and becomes hyperphosphorylated upon Wnt signaling (Willert et al 1997;Peters et al 1999;Kishida et al 2001;Cong et al 2004a;Klein et al 2006). These kinases, in particular CK11, have been documented to have activating roles in Wnt/b-catenin signaling, but the role of DVL phosphorylation remains unclear.…”
Section: The Wnt -Fzd -Lrp5/6 Complexmentioning
confidence: 99%
“…Genes encoding the core b-catenin destruction complex components CK1a (kin-19) (Peters et al 1999), GSK3b (gsk-3) (Schlesinger et al 1999), Axin ( pry-1 and axl-1) Korswagen et al 2002;Oosterveen et al 2007), and APC (apr-1) (Rocheleau et al 1997) are found in C. elegans. In the case of Axin and APC, the encoded proteins are fairly diverged from family members in other species, with several conserved domains absent.…”
Section: Destruction Complex: Both Negative and Positive Roles In Wntmentioning
confidence: 99%
“…Interestingly, the CK1 family shows a strong preference both in vitro and in vivo for 'primed,' pre-phosphorylated substrates (Cheong & Virshup 2011). Considering the broad distribution of CK1 family members and their substrates, these kinases have been found to participate in many biological activities, such as Wnt signaling (Peters et al 1999;Price 2006), biological rhythm (Etchegaray et al 2009;Lee et al 2009), DNA repair (Dhillon & Hoekstra 1994), and the cell cycle (Behrend et al 2000;Petronczki et al 2006). The Arabidopsis thaliana genome was found to contain 14 casein kinase 1-like (CKL) genes, and, within the conserved kinase domains, they share 89% sequence similarity at the aa level.…”
Section: Introductionmentioning
confidence: 99%